TECTONIC GEOMORPHOLOGY OF ESCARPMENTS: THE CASES OF KOMPOTADES AND ΝΕΑ ANCHIALOS FAULTS - Zovoili, E.; Konstantinidi, E.; Koukouvelas, I. K. (Bulletin of the Geological Society of Greece, 2004)
Most active processes on the surface imply that tectonics and geomorphology converge in a way that landscape change may be used as a tectonic signal, given that erosion and weathering have been taken into account. We selected two faults, the Kompotades and the Nea Anchialos faults in the Sperchios and South Thessaly rift zones respectively, and we performed a morphometric analysis. This analysis comprises geomorphic indices that have been used successfully in studies of active tectonics, as the mountain front sinuosity index (Smf), stream gradient index (SL) and valley floor width to valley height ratio (Vf). At both studied mountain fronts, the Vf index ranged between 0,4 to 1,2, implying high uplift rates, while the Smf «1 index revealed relatively high tectonic activity, which decreases towards the west. On the other hand, the SL index though more sensitive to non-tectonic processes, (i.e. the rock resistance, stream length) is less indicative of tectonic activity. Based on the distribution of the geomorphic indices a two-fault strand model is suggested forming the mountain front in the two examples with the range-ward fault strand to be more appropriate for Kompotades fault and the basinward fault strand for Nea Anchialos fault.